Assessing the relationship of paraoxonase-1 Q192R polymorphisms and the severity of lung disease in SM-exposed patients. (June 2013) - Golmanesh, Leila; Bahrami, Farideh; Pourali, Fatemeh; Vahedi, Ensieh; Wahhabaghai, Hannaneh; Mehrani, Hossein; Ghanei, Mostafa
Abstract Late respiratory complications in patients suffering from pulmonary lesions due to sulfur mustard (SM) gas are asthma, chronic obstructive pulmonary disease and bronchiectasis. Recently PON1 antioxidant activity draws attention as the enzyme which prevents the oxidation of lipoproteins during oxidative stress. In this study we aimed to investigate PON1 192 polymorphisms and paraoxonase and arylesterase activity in the serum of SM-exposed lung disease patients. Also, we examined the detection of PON1 and apoA1 proteins in BAL fluid. 101 male patients were included who were categorized to three groups of mild, moderate and severe suffering from pulmonary lesions due to SM. Significant reduction in paraoxonase activity [Healthy: 412.46 ± 89.1 U/L, Severe: 89.66 ± 20.7 U/L] (p < 0.0001) and arylesterase activity [Healthy: 25826.4 ± 4425.23 U/L, Severe: 16760.43 ± 3814.9 U/L] (p < 0.0001) with increase in severity of disease was demonstrated statistically. With respect to the distribution of the PON1 polymorphism, the RR genotype was more frequent in severe patients [37.2%] than healthy group [10%] (p < 0.05) and no significant regression was found between genotype and PON1 activity. On the other hand, the results of PON1 and apoA1 detection illustrated that only apoA1 protein was found in BAL fluid. According to our findings it seems that increase in the stress oxidative in chemical injured veterans with pulmonary complications comes with reduction in PON1 enzyme activity and appearance of RR genotype rises up with the increase in disease severity. Since a significant correlation between enzyme activity and genotype was not observed altering these two variables with each other requires more studies.